The Flipped-Blended Model for STEM Education to Improve Students’ Performances - Wibawa, Basuki; Kardipah, Seipah (International Journal of Engineering and Technology, 2018)
Flipped-Blended model, a combination of flipped classroom and blended learning environment, has become increasingly popular, especially in K-12 education. Flipped-Blended model takes advantage of technology for a more flexible learning environment and facilitates a more learner-centered as well as a more active learning in classroom. Flipped-Blended can be seen as an innovation and a new learning paradigm. This is more than just flipped the in-class and out-class activities, the flipped-blended also change the passive learning into active learning. This model can work well for STEM education due to its active learning and learner-centered nature. Thus, students can explore themselves in class by doing lab work or doing research in small group or individuals. Research method used was a descriptive method. This conceptual paper describes many of the characteristics of flipped-blended model and STEM education. The paper concludes by proposing a flipped-blended theoretical model and offers recommendation regarding implementation in STEM Education.Â Â